Molecular Evolution of HIV-1 CRF01_AE Env in Thai Patients - Boonchawalit, Samatchaya (Public Library of Science, 2011)
BACKGROUND: The envelope glycoproteins (Env), gp120 and gp41, are the most variable proteins of human immunodeficiency virus type 1 (HIV-1), and are the major targets of humoral immune responses against HIV-1. A circulating recombinant form of HIV-1, CRF01_AE, is prevalent throughout Southeast Asia; however, only limited information regarding the immunological characteristics of CRF01_AE Env is currently available. In this study, we attempted to examine the evolutionary pattern of CRF01_AE Env under the selection pressure of host immune responses. METHODOLOGY/PRINCIPAL FINDINGS: Peripheral blood samples were collected periodically over 3 years from 15 HIV-1-infected individuals residing in northern Thailand, and amplified env genes from the samples were subjected to computational analysis. The V5 region of gp120 showed highest variability in several samples over 3 years, whereas the V1/V2 and/or V4 regions of gp120 also showed high variability in many samples. In addition, the N-terminal part of the C3 region of gp120 showed highest amino acid diversity among the conserved regions of gp120. Chronological changes in the numbers of amino acid residues in gp120 variable regions and potential N-linked glycosylation (PNLG) sites are involved in increasing the variability of Env gp120. Furthermore, the C3 region contained several amino acid residues potentially under positive selection, and APOBEC3 family protein-mediated G to A mutations were frequently detected in such residues. CONCLUSIONS/SIGNIFICANCE: Several factors, including amino acid substitutions particularly in gp120 C3 and V5 regions as well as changes in the number of PNLG sites and in the length of gp120 variable regions, were revealed to be involved in the molecular evolution of CRF01_AE Env. In addition, a similar tendency was observed between CRF01_AE and subtype C Env with regard to the amino acid variation of gp120 V3 and C3 regions. These results may provide important information for understanding the immunological characteristics of CRF01_AE Env.